Eksplorasi Scientific Explanation Berdasarkan Tingkat Kemampuan Peserta Didik - Hernita A; Supriyono Koes Handayanto; Edi Supriana (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This descriptive quantitative study aims to discern students' scientific explanation skills. The researcher took 76 students from Senior High School 3,4, and Islamic Senior High School 1 in Malang city as samples. Six essay questions with coefficient reliability 0.6 were used as instruments in this study. The findings show that high initial ability of students' reasoning skills was very good due to the fact that they could associate claim and evidence. Meanwhile, students with low initial ability relied upon their instinct in constructing the evidence; therefore, theie reasoning skill was low.Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan scientific explanation peserta didik. Penelitian ini berupa kuantitatif deskriptif dengan sampel sebanyak 76 peserta didik yang berasal dari SMA Negeri 3 dan 4, serta MAN 1 di Malang. Penggunaan instrumen berupa soal uraian sebanyak enam soal yang memperoleh koefisien reliabilitas 0,6. Kemampuan reasoning peserta didik pada ketgori kemampuan awal tinggi sangat baik karena peserta didik sudah mampu menghubungkan claim dan evidence. Peserta didik kemampuan awal rendah masih mengandalkan insting daripada data dan bukti dalam menyusun evidence sehingga mereka memiliki reasoning yang masih rendah.